Towards a criminology of atmospheres: law, affect and the codes of the street - Fraser, Alistair (2021)
The street has a long and distinguished pedigree in criminology as a site of human sociability, transgression and spontaneity. Recent scholarship in legal studies has, however, explored the role that non-human actors play in the normative ordering of urban life. These interventions suggest the need for criminologists of the street to take seriously not only the experiential foreground of crime but also its background. In this article, we seek to bring these traditions into dialogue through engagement with the concept of ‘atmosphere’ – a place-based mood or spatialised feeling that blends human and non-human elements, and has the capacity to act in a quasi-agentic manner. Drawing on an experiment in ‘atmospheric methods’ conducted during Hong Kong’s pro-democracy Umbrella Movement, in which some of the city’s central streets were occupied for 79 days, we seek to demonstrate that the analytics of ‘atmosphere’ offers a unique conceptual approach to urban life and street crime in the contemporary age